If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(1 + -10n) = -27 + 14b (1 * -2 + -10n * -2) = -27 + 14b (-2 + 20n) = -27 + 14b Solving -2 + 20n = -27 + 14b Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 20n = -27 + 2 + 14b Combine like terms: -2 + 2 = 0 0 + 20n = -27 + 2 + 14b 20n = -27 + 2 + 14b Combine like terms: -27 + 2 = -25 20n = -25 + 14b Divide each side by '20'. n = -1.25 + 0.7b Simplifying n = -1.25 + 0.7b
| 0.6x+1.43=x-6.22 | | 6(4b+2)+3b=-27+14b | | (2/3x)-4=5/6 | | 2/3x-4=5/6 | | 5x-25=2x-38 | | -26=4(8n+6)-2(3n-1) | | 7(7k-9)+5k=8k+29 | | 2(-2p+3)-5(p+7)=34 | | -54/g=3 | | 7a-3b+5= | | -34+x=6(-8-x) | | 6x/-4=-.3 | | -23-8x=-2(x-7)-7 | | (y^4/5)^2 | | 7900=40x+4000 | | k-4=-7 | | 3(2x-1)=3-2(x-1) | | 4=22x | | -2.2d+16.95=-3.8d-14.41 | | d/-7-8 | | -18+c=-14 | | differentiate:dy/dx=3x^2 | | f(2.3)= | | [(2x-5)/5]-13-x | | Y=9x-2x^2 | | 0.25r+0.75=0.5r | | 2(z+5)-2z=7 | | 6x+5y-7x-8y+4= | | 3a+4a=31 | | ((2x-5)/5)-13-x | | 12-(7+4)= | | 125=25^3/2 |